Creeds and confessions of faith in the Christian tradition - Pelikan, Jaroslav Jan, 1923-; Hotchkiss, Valerie R., 1960- (New Haven and London : Yale University Presss, 2003)
Contents: v.1. Rules of faith in the early church. Eastern Orthodox affirmations of faith. Medieval Western statements of faith. v.2. Creeds and confessions of the reformation era. v.3. Statements of faith in modern Christianity. v.4. Credo
Includes bibliographical references and indexes
Keywords: Creeds; Creeds -- History and criticism